Analytical Study of climate changes effect on wind speed in Al- Nasiriya, Iraq - Khamees, Ahmed B.; Nassir, Sura T.; Heni, Khalid S. (Iraqi Journal of Science, 2018)
The ambient temperature is the major parameter that influences wind speed. When temperature rises, air will be extended and wind will flow with different speeds in all directions, increasing of temperature means that wind speed will be increased and vice versa. The relative humidity and atmospheric pressure affected with temperature, too. Climate changes making significant effects on the atmospheric temperature. In this project, the data of thirty four years (1981 – 2004) has been analyzed to get an idea about the changes occurred in the meteorological parameters in Al-Nasiriya city, which was chosen because it has a distinctive wind speed.